Geodetic investigation of the 13 May 1995 Kozani-Grevena (Greece) earthquake - Clarke, P; Paradissis, D; Briole, P; England, P; Parsons, B; Billiris, H; Veis, G; Ruegg, J (1997)
The Ms = 6.6 13 May 1995 Kozani - Grevena earthquake struck a region of low historical seismic activity which includes a 10-year-old triangulation network in northern Greece. After the earthquake, monuments from this network were occupied with GPS to measure co-seismic displacements. Inversion of the co-seismic displacement field to yield a source mechanism is achieved by use of a hybrid simplex - MonteCarlo method which requires no a priori constraints. The model focal mechanism agrees well with the global CMT solution and locally observed aftershocks, but implies a significantly higher scalar moment than do seismological or SAR. interferometry studies, and has a longer fault length than the model based on SAR interferometry.